The Role of Support and Follow-up in Improving the Effectiveness of Continuous Training Implementation for Teachers - Oluwatosin, Adebayo (Metromedia, 2022)
Continuous training for teachers is one way to improve their pedagogical skills and the quality of their teaching. However, supporting factors such as a lack of follow-up after training can affect the effectiveness of the implementation of knowledge gained by teachers in the classroom learning process. This study aims to examine the extent to which a lack of support and follow-up affects the use and application of skills gained in training by teachers. This study was conducted using a literature study approach, analyzing various previous studies regarding the effect of post-training support on teaching practices. The results of the study indicate that without follow-up and ongoing support, teachers tend to have difficulty implementing new knowledge in dynamic classroom situations. Limitations in access to mentoring or communities of practice as well as inadequate evaluation hinder teachers from reflecting on and adjusting the teaching strategies they have learned. For this reason, it is recommended that educational institutions provide continued support for teachers, such as mentoring, learning communities, and ongoing evaluation to improve the effectiveness of learning and the quality of teaching. With consistent support, it is hoped that teachers will be able to make optimal use of training, improve the quality of teaching, and, ultimately, student learning outcomes.